A Novel Hysteresis Model of Magnetic Field Strength Determined by Magnetic Induction Intensity for Fe-3% Si Electrical Steel Applied in Cigarette Making Machines. (18th October 2016) - Wang, Hao; Zhan, Jianbo; Yu, Zhenhua; Zhang, Ying; Yu, Jiang; Gui, Yongfa; Yu, Tingting; Xie, Jiao; Zhang, Hongkui; Ji, Yafeng; Zan, Na; Fu, Rongrong; et al.
Abstract : Hysteresis characteristics of grain-oriented electrical steel were studied through the hysteresis loop. Existing hysteresis fitting simulation methods were summarized, and new Fe-3% Si grain-oriented electrical steel hysteresis loop model was proposed. Undetermined coefficients of the magnetic field intensity and magnetic flux density were determined by both the fixed angle method and the least squares method, and the hysteresis loop model was validated with high fitting degree by experimental data.